Periplanta americana extract regulates the Th17/Treg cell balance via Notch1 in ulcerative colitis - Yanqiu Zheng; Yanqiu Zheng; Huibiao Li; Shiyu Qi; Fan Xiao; Jinbin Song; Shiyin Liu; Xinlin Chen; Yanwu Li; Muyuan Chen (Frontiers in Pharmacology)
BackgroundPeriplanta americana extract (PAE), a traditional Chinese medicine (TCM) from Shen Nong Ben Cao Jing, has been used to treat ulcerative colitis (UC), various types of wounds and ulcers, infantile malnutrition, palpitation, asthma, and so on. However, the exact mechanisms of PAE in UC have still not been fully revealed. The study aims to explore the therapeutic effects and mechanisms of PAE in UC.MethodsThe efficacy of PAE was evaluated using a DSS-induced UC mice model and the colon inflammation and mucosal barrier were comprehensively assessed. Furthermore, Network pharmacological analysis was utilized to identify potential targets and signaling pathways of PAE in the UC treatment. The proportion and the markers of Th17 and Treg cells in the spleen and colon were examined. The signal transduction was detected in vivo. In vitro, an activated Notch1-mediated Th17/Treg was modeled, and the effect of PAE on the epithelial cell barrier was examined.ResultsPAE mitigated colon inflammation and intestinal barrier damage in UC mice. Network pharmacological analysis showed that the targets of UC intervention by PAE may be closely related to Th17 cell differentiation, the IL-17 signaling pathway, and cytokine-cytokine receptor interaction. Mechanistically, PAE regulated the balance of Th17/Treg and inhibited the Notch1/Math1 pathway in the colon of UC mice. In vitro, PAE intervention alleviated the activated Notch1-mediated Th17/Treg imbalance in Jurkat T cells. After notch1-activated Jurkat T cells were co-cultured with HCoEpic cells, the expressions of Occludin, ZO1 were higher in the HCoEpic cells.ConclusionPAE could alleviate colon inflammation and mucosal barrier damage in UC, which are related to the inhibition of Notch1 and the regulation of the Th17/Treg balance. PAE might be a potential candidate agent for UC treatment.